Concepção de linguagem, de texto e de gêneros discursivos na formação inicial do professor de Língua Portuguesa: um estudo de cursos de licenciatura em Letras. - Souza, Tatiana Fasolo Bilhar de (2018)
The Portuguese language (PL) teaching in our country, since the publication of the National Curriculum Parameters (PCN) (BRAZIL, 1998), has been guided by the interactionist conception of language, which presupposes the work, in the classroom, from real situations of language use. In light of this document, the State of Paraná published the Curricular Guidelines for Basic Education (DCE) in 2008, which in its section on teaching PL (DCELP) is guided by the linguistic ideas of the Bakhtin Circle. This paper shares an interactionist and dialogical conception of language, with a focus on discourse as social practice, comprehends the text in its condition of utterance and guides the use of speech genres in the classroom as tools for teaching PL. However, in order to be able to implement this proposal in pedagogical practice, it is necessary that PL teachers receive, starting at the undergraduate level, a formation consistent with these purposes. In order to deal with this subject, it is necessary that we turn our researcher's gaze towards the initial formation of Language Arts teachers. Therefore, this paper analyses two Language Arts undergraduate courses from the State University of Western Paraná (Unioeste), one in the campus Foz do Iguaçu and the other in the campus Marechal Cândido Rondon, to answer the following question: Is there a dialogue between the syllabuses and the Political Pedagogical Project (PPP) of the courses aimed at the training of LP teachers according to the DCELP? To answer it, our general objective is an attempt to relate the theoretical and methodological orientations of the DCELP to the PPP and to the syllabuses of two Language Arts courses at Unioeste, observing the conception of language, text and speech genres that guide the initial formation of PL teachers, within the socio-historical context of Language Arts undergraduate courses in Brazil. In order to fulfill this investigative purpose, we performed a qualitative and interpretive research enrolled in Applied Linguistics field, which has a documental analysis of the PPP and eight syllabuses of the courses analyzed – three from the course of Marechal Cândido Rondon and five from the course of Foz do Iguaçu. The theoretical framework is based on authors of the Bakhtin Circle – such as Bakhtin and Volochinov (2014 [1929]), Volochinov (2013 [1930]) and Bakhtin (2011 [1979]) – as well as others who explain their theories – Rodrigues (2001, 2005), Faraco (2009), Rodrigues and Cerutti-Rizzatti (2011) and Miotello (2014). We also rely on authors such as d'Ávila (2007) and Nóvoa (1992, 2009) to think about initial formation and its relation to teaching and authors such as Almeida Filho (2008) and Cavalcanti (2013) to discuss teacher formation. The results indicate that both courses have a relationship with the DCELP, but that it happens differently. The course in Foz do Iguaçu is guided by the same conceptions of language, text and genres of the state pedagogical document, so that some of its disciplines not only discuss the PL teaching proposal of the DCELP, but also propose a study of the speech genres subsidized by their conceptions. Even though the course in Marechal Cândido Rondon is based on an interactionist conception of language, it adopts an organizing axis for the disciplines of PL contrary to the Bakhtinian premises for the study of language. Therefore, it establishes dialogue with the DCELP in some disciplines, but this relation is more in the sense of discussing the proposal of the document and the theories and conceptions that subsidize it than to guide its disciplines by these conceptions.